Adoption of the Q transcriptional regulatory system for zebrafish transgenesis - Subedi, Abhignya; Macurak, Michelle; Gee, Stephen T.; Monge, Estela; Goll, Mary G.; Potter, Christopher J.; Parsons, Michael J.; Halpern, Marnie E. (Methods (San Diego, Calif.), 2014)
•Q transcriptional regulatory system of Neurospora crassa functions in zebrafish.•Tissue-specific QF driver lines activate a QUAS:GFP transgenic reporter.•Silencing of QUAS-regulated transgenes not observed in F4 generation.•Q reagents cloned into Tol2 Gateway vectors for ease of use and distribution. The Gal4–UAS regulatory system of yeast is widely used to modulate gene expression in Drosophila; however, there are limitations to its usefulness in transgenic zebrafish, owing to progressive methylation and silencing of the CpG-rich multicopy upstream activation sequence. Although a modified, less repetitive UAS construct may overcome this problem, it is highly desirable to have additional transcriptional regulatory systems that can be applied independently or in combination with the Gal4/UAS system for intersectional gene expression. The Q transcriptional regulatory system of Neurospora crassa functions similarly to Gal4/UAS. QF is a transcriptional activator that binds to the QUAS upstream regulatory sequence to drive reporter gene expression. Unlike Gal4, the QF binding site does not contain essential CpG dinucleotide sequences that are subject to DNA methylation. The QS protein is a repressor of QF mediated transcriptional activation akin to Gal80. The functionality of the Q system has been demonstrated in Drosophila and Caenorhabditis elegans and we now report its successful application to a vertebrate model, the zebrafish, Danio rerio. Several tissue-specific promoters were used to drive QF expression in stable transgenic lines, as assessed by activation of a QUAS:GFP transgene. The QS repressor was found to dramatically reduce QF activity in injected zebrafish embryos; however, a similar repression has not yet been achieved in transgenic animals expressing QS under the control of ubiquitous promoters. A dual reporter construct containing both QUAS and UAS, each upstream of different fluorescent proteins was also generated and tested in transient assays, demonstrating that the two systems can work in parallel within the same cell. The adoption of the Q system should greatly increase the versatility and power of transgenic approaches for regulating gene expression in zebrafish.